Celebrity Endorsements in an Indian Perspective : A Review - Sharma, Yogita (Indian Journal of Marketing, 2016)
The use of celebrities as endorsers is an important concept of the modern marketing strategy for brand promotions. Celebrity endorsements increase the sales and mutually benefit organizations/brands, the celebrities themselves, and the advertisement companies that produce attractive, influencing, and mind blowing advertisements. The impact of a celebrity endorsement is affected by a number of factors including the image and popularity of a celebrity, a proper match between a product and a celebrity, the attractiveness of the advertisement, and the frequency of the advertisement in electronic and print media. The role of the celebrity endorsement in affecting brand value, consumers’ behaviour toward purchasing, match and mismatch between a celebrity and a brand, and the various advantages and disadvantages of the concept of celebrity endorsement were discussed in this paper.